PENGEMBANGAN SISTEM PENGENDALIAN ARUS KAS MENGGUNAKAN METODE DIRECT CASH FLOW (STUDI KASUS : BADAN KESATUAN BANGSA DAN POLITIK DAERAH PROVINSI LAMPUNG) - Dedi Darwis; Cici Dian Paramita; Ikbal Yasin; Heni Sulistiani (Jurnal Ilmiah Sistem Informasi Akuntansi, 2022)
The study, entitled Accounting Information Systems Cash Flow Control Direct Cash Flow Method (Case Study: National Unity and Political Agency of Lampung Province) in the process of controlling the flow of funds in the finances of the National Unity and Political Agency of Lampung Province found problems including the recording process on the finance department uses a ledger (manual recording). Using the ledger (recording) causes the recording to be less effective and also takes a long time. This study aims to facilitate the finance department in the process of managing funds. Data collection techniques include observation, interviews, documentation, and literature review. The system development method used in this research is the Prototype method using UML (Unified Modeling Language) as a tool to analyze the system to be made including Use Case Diagrams, Activity Diagrams and Class Diagrams. The development of this system uses the PHP programming language, Codeigniter framework version 3.1, Sublime as a Text editor version 3.1.1 (64 bit), and MySQL database version 11.11 (64 bit) as a database management system. The results of this study are able to build web-based applications and can manage financial transactions and present financial reports quickly and well, which has been tested by Blackbox and obtained a percentage with a value of 100%, and results that the system can run according to user needs and is feasible to use workable